The mortality of captive flamingos at Slimbridge 1975-89 - Brown, Martin J; Pickering, Simon P C (Wildfowl, 1992)
Generally, captive flamingos appear to be relatively healthy in comparison with other captive wildfowl at Slimbridge. During the period 197-89, a total of 131 dead flamingos was examined. Renal failure (21.3%) and cardiac failure (16.8%) were the most common causes of death followed by trauma (10.6%) and foot infections (10.6%). The pattern was generally similar between species. James' and Lesser Flamingos had significantly higher mortality rates than Greater, Chilean and Andean Flamingos. The majority (75%) of flamingo deaths occurred during the winter and spring when birds spend more time in their winter housing. Although the houses are heated, the lower temperature may be a contributory factor; the level of stress within the flock may also be higher when the birds are in an enclosed house.